Beyond assimilation and refusal: a Warlpiri perspective on the politics of recognition. Issue 1 (2nd January 2017) - Hinkson, Melinda
ABSTRACT: This paper takes up the concept of recognition as an ever-present structuring arrangement in relations between Aboriginal and non-Aboriginal people. Recognition, in both positive and negative guises, is understood here to foreclose the terms of those relations. For Warlpiri people of Central Australia who have achieved positive recognition and the attendant confirmation of legal rights in land and native title, the contradictions and frustrations of recognition continue to be multiple. Looking back across the eight decades since Warlpiri were first recognised in particular ways by settler-colonists, the paper explores a series of encounters where transformation is visible but ultimately undermined. The paper explores these issues by way of the observations of one remarkable cross-cultural innovator and his quest to 'be free to the world'. In tracing this work of interpretation and its strategic application to the field of intercultural relations the paper argues that what is being pursued should not be mistaken for assimilation, nor the refusal of recognition, but rather a mode of reciprocal engagement that carries with it significant transformative potential.